PERAN PANCASILA DALAM MEMBANGUN KEPEMIMPINAN YANG BERETIKA DI DUNIA MANAJEMEN - Br Sitepu RG, R Patrecia (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Pancasila, as the foundational philosophy of Indonesia, plays a strategic role in fostering ethical leadership, particularly in the field of management. The noble values of Pancasila, encompassing Belief in One Supreme God, Just and Civilized Humanity, Unity of Indonesia, Democracy Guided by the Inner Wisdom of Deliberation/Representation, and Social Justice for All Indonesians, serve as a critical foundation for shaping leaders’ ethics and morality. In the context of management, the application of Pancasila’s values assists leaders in navigating global challenges such as economic pressures, cultural diversity, and conflicts of interest. Ethical leadership rooted in Pancasila promotes an inclusive, fair, and welfare-oriented workplace environment. The value of Divinity encourages leaders to act with integrity and responsibility, while humanity ensures respect for human rights and social justice. Unity becomes key to building strong teamwork, and democracy supports decision-making processes based on deliberation. This article highlights the importance of internalizing Pancasila as an ethical guideline for leaders in various organizations to build trust, inspire teams, and achieve sustainable business outcomes. Thus, Pancasila is not only relevant on a national scale but also has the potential to serve as a model for ethical leadership on a global level.